2022
DOI: 10.3389/fnmol.2022.889641
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach in Autism Spectrum Disorders: From Sensory Processing to Behavior Problems

Abstract: Atypical sensory processing described in autism spectrum disorders (ASDs) frequently cascade into behavioral alterations: isolation, aggression, indifference, anxious/depressed states, or attention problems. Predictive machine learning models might refine the statistical explorations of the associations between them by finding out how these dimensions are related. This study investigates whether behavior problems can be predicted using sensory processing abilities. Participants were 72 children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In other words, our results suggest that some items in the sensory processing patterns of ASD patients are strongly associated with emotional/behavioral problems, while others are weakly associated with emotional/behavioral problems. These findings are consistent with a recent study in Spain that examined the ability of machine learning to predict behavioral problems from sensory profiles [16]: 72 ASD-affected children (51 boys, 21 girls) aged 6-14 years were included, and their parents' responses to the SP2 and CBCL were used to predict CBCL outcomes from SP2 scores. The results showed that (i) sensory avoiding in the SP2 predicted 'anxious/depressed' and aggressive behavior in the CBCL, and (ii) low registration in the SP2 predicted 'withdrawn/depressed,' social problems, and internalizing [16].…”
Section: Discussionsupporting
confidence: 89%
“…In other words, our results suggest that some items in the sensory processing patterns of ASD patients are strongly associated with emotional/behavioral problems, while others are weakly associated with emotional/behavioral problems. These findings are consistent with a recent study in Spain that examined the ability of machine learning to predict behavioral problems from sensory profiles [16]: 72 ASD-affected children (51 boys, 21 girls) aged 6-14 years were included, and their parents' responses to the SP2 and CBCL were used to predict CBCL outcomes from SP2 scores. The results showed that (i) sensory avoiding in the SP2 predicted 'anxious/depressed' and aggressive behavior in the CBCL, and (ii) low registration in the SP2 predicted 'withdrawn/depressed,' social problems, and internalizing [16].…”
Section: Discussionsupporting
confidence: 89%